Starry night pro - Boime, Albert (Toronto : Space.com., 2000)
Windows XP.
Features views from any location on Earth, or from any planet, moon, comet, asteroid or satellite. A planetarium program and sky simulator.
Keywords: Interactive multimedia; CD-ROMs.; Astronomy -- CD-ROMs.; Solar system -- CD-ROMs.